National Survey of Youth, 1967 - Gold, Martin ([Verlag nicht ermittelbar], 1984)
This study contains data that measure the frequency and seriousness of delinquent activities among American youths aged 13-16 in 1967. Respondents were asked to indicate which of 16 offenses they had committed in the previous three years and were then asked detailed follow-up questions about the circumstances of each offense that they reported. Respondents' reports of delinquency were then checked against the official delinquency records. Respondents were also asked about their attitudes toward school, school grades, peer group activities, job aspirations, dating habits, and self-perception. Also elicited was information about respondents' family characteristics, such as relationship with their parents, parents' education, job history, and family size. Demographic variables specify sex, date of birth, race, education, nationality, and religion. The study contains two data files. The individual respondent is the unit of analysis in the Main File (Part 1), and the offense is the unit of analysis in the Offenses File (Part 2).